Prospects of Inhaled Phage Therapy for Combatting Pulmonary Infections - Wang, Xiang; Xie, Zuozhou; Zhao, Jinhong; Zhu, Zhenghua; Yang, Chen; Liu, Yi (Frontiers in Cellular and Infection Microbiology, 2021)
With respiratory infections accounting for significant morbidity and mortality, the issue of antibiotic resistance has added to the gravity of the situation. Treatment of pulmonary infections (bacterial pneumonia, cystic fibrosis-associated bacterial infections, tuberculosis) gets more challenging with the involvement of multi-drug resistant bacterial strains being the etiological agents. Further, with the dearth of new antibiotics available and old antibiotics losing efficacy, it is prudent to switch to non-antibiotic approaches to fight this battle. Phage therapy represents one such approach that has proven efficacy against a range of bacterial pathogens including drug-resistant strains. Inhaled phage therapy encompasses the use of stable phage preparations given via aerosol delivery. This therapy can be used as an adjunct treatment option in both prophylactic as well as therapeutic modes. In the present review, we highlight firstly the role and action of phages against pulmonary pathogens followed by delineating the different methods of delivery of inhaled phage therapy with evidence of success. Further, the review aims to focus on the recent advances and developments made in improving the final success and outcome of pulmonary phage therapy. It details the use of electrospray for targeted delivery, advances in nebulization techniques, individualized controlled inhalation with software control, and liposome-encapsulated nebulized phages to take pulmonary phage delivery to the next level. The review would thus enable to expand the knowledge of the researchers and scientific community on pulmonary delivery of phages and advances made for improved outcomes in the treatment of respiratory infections.